A escrita de alunos com transtorno do espectro autista leve - Weisheimer, Irací Casemiro (2019)
Our research has as a general aim to analyze how students with mild Autism Spectrum Disorder (hereafter, mild ASD) handle language in written records at school. It was interesting for us as well to understand if the characteristics of this disorder, such as social interaction failure, difficulty in fine motor skills and obsessive interests are manifested in the texts of the students studied, this being our specific objective. Even though a substantial research group exposes the benefits of including people with autism, this issue still remains controversial, especially as regards the possibility for schools to provide adequate responses to the educational needs of students with disabilities. Considering that language is the mediator of this process, the research is theoretically anchored in the historical-cultural perspective of human development, established by Vygotsky (1989, 2003), articulated to the studies of Bakhtin (2003, 2004) in the fields of semiotics. The question of our research is: how do students with mild ASD handle writing in their texts at school? It is a documentary research, whose corpus contains texts written by students with mild ASD. It is a research located in the Applied Linguistics because it focuses the use of the language in a situation of school writing. The authors of the research texts are students of Elementary School (6th to 9th grade), diagnosed and with a clinical report of mild ASD from four (4) schools from the urban area of the public school system from a city of the West region of Paraná. The procedures to obtain the texts followed what was established by the Committee of Ethics in Research (CER, according statement number 2.924.305-2018). Texts from seven (7) students were analyzed, numbering fifteen (15) texts. The research is qualitative, descriptive and interpretative (TRIVIÑOS, 1987) since we are concerned about the comprehension and interpretation of the writing behavior of students with mild ASD. We analyzed the texts which make the corpus, considering the three constitutive elements of discourse genders: the thematic content, the compositional construction and the style (BAHKTIN, 2003). Then, we analyze if the writing of these texts presents characteristics that may be due to mild ASD, considering for this purpose bibliographies of the health area, which describe about the disorder. We have observed in literature on mild ASD that the fine motor coordination of people with this disorder is deficient. However, research has shown us that, except in the written production of one (1) student, there were no texts with significant problems in relation to the letter layout. On the contrary, we realize that in seven (7) texts the letter layout favored readability. It was found in nine (9) texts a rigid relationship with the handling of written language, with many details for possibly being a subject of interest to the student author, derived from the mild stereotypes proper of mild ASD, we noticed in nine (9) texts, typical feature of mild TEA. We believe that our work may contribute clues that will guide future research aimed at understanding the language of people with mild ASD.